2022
DOI: 10.3390/plants11131724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urea Coated with Polyaspartic Acid on the Yield and Nitrogen Use Efficiency of Sorghum (Sorghum bicolor, (L.) Moench.)

Abstract: Innovative approaches to enhance N fertilization to improve season-long N availability are essential to optimal sorghum (Sorghum bicolor, (L.) Moench.) productivity and N use efficiency. A two-year field experiment was conducted in the 2020 and 2021 summer seasons on the North China Plain to determine the effects of a novel urea coated with polyaspartic acid (PAA) (PN) and a control treatment (CN) on grain sorghum yield and N utilization characteristics at four N application rates (0, 60, 120, and 240 kg ha−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…It could chelate a variety of nutrient elements, promote the absorption and utilization of fertilizer, and effectively promote the nitrogen metabolism of crops. Recent research has indicated that PASP combined with urea could increase nitrogen accumulation in the upper part of sorghum, and improve nitrogen use efficiency and grain yield [8]; increase NR activity and promote nitrogen assimilation in maize seedlings [35]; and increase the activities of enzymes of nitrogen metabolism and the content of soluble protein in functional leaves of rice [21]. CTS, the other component of PAC, also has good adsorption and sustained-release effects, which can accelerate life activities of microorganisms in soil, promote soil respiration, improve nutrient availability [9], and the fertilizer absorption efficiency of plants [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could chelate a variety of nutrient elements, promote the absorption and utilization of fertilizer, and effectively promote the nitrogen metabolism of crops. Recent research has indicated that PASP combined with urea could increase nitrogen accumulation in the upper part of sorghum, and improve nitrogen use efficiency and grain yield [8]; increase NR activity and promote nitrogen assimilation in maize seedlings [35]; and increase the activities of enzymes of nitrogen metabolism and the content of soluble protein in functional leaves of rice [21]. CTS, the other component of PAC, also has good adsorption and sustained-release effects, which can accelerate life activities of microorganisms in soil, promote soil respiration, improve nutrient availability [9], and the fertilizer absorption efficiency of plants [16].…”
Section: Discussionmentioning
confidence: 99%
“…Also, PASP has notable properties of low production costs and biodegradation [6]. Because of the advantages above, PASP has been widely applied in agriculture as the absorption promoter of fertilizers, a controlled-release agent, and so on [7,8]. CTS is a derivative of chitin and is considered the second most common polymer in the world after cellulose [9].…”
Section: Introductionmentioning
confidence: 99%
“…Polyaspartic acid (PASP) has a strong absorption capacity for nutrient ions because of the numerous free carboxyl and amide groups in its molecular chains [6]. Thus, PASP can reduce nutrient loss and increase the soil nutrient content [7,8]. PASP has shown a high capacity to stimulate crop growth and nutrient uptake and strengthen crop stress resistance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PASP can be used as a controlled-release agent and absorption promoter in fertilizers [7,11] and has become a widely used bioactive organic synergist for high-efficiency urea in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation